2008
DOI: 10.2215/cjn.03660807
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Live Donors by Candidates for Kidney Transplantation

Abstract: Background: Little is known about efforts that renal transplant candidates make to recruit live donors. It was hypothesized that preference for live donor kidney transplantation and greater knowledge about live donor transplantation are associated with candidates' initiating conversations about donation with potential donors.Design, setting, participants, & measurements: A cross-sectional study of renal transplant candidates was performed at initial transplant evaluation. Candidates completed a questionnaire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 30 publications
3
61
0
Order By: Relevance
“…Whereas our overall percentage of black patients interested in either DDKT or LDKT (72.3%) was almost identical to an earlier study (2), our study diverges from previous studies (2,4,7,(13)(14)(15) in that significantly more black men (82.8%) wanted LDKT compared with women (58.6%). Although there is some evidence that age may affect attitudes toward transplantation (2), younger women were less likely to want LDKT compared with younger men.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Whereas our overall percentage of black patients interested in either DDKT or LDKT (72.3%) was almost identical to an earlier study (2), our study diverges from previous studies (2,4,7,(13)(14)(15) in that significantly more black men (82.8%) wanted LDKT compared with women (58.6%). Although there is some evidence that age may affect attitudes toward transplantation (2), younger women were less likely to want LDKT compared with younger men.…”
Section: Discussionsupporting
confidence: 71%
“…The results are on the basis of a convenience sample of 101 urban-dwelling black patients with ESRD at two hemodialysis clinics affiliated with a university hospital in north Philadelphia that serve a largely minority lowincome patient population (53). Despite their comparatively high rate of transplant referral, our patients are similar to other patients in that many do not complete the workup step toward the waitlist (13,16,48). Although other studies show that patients with private insurance have better access to LDKT (24,25), only two of our patients had private insurance, and neither wanted an LDKT.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…with a potential donor (Reese et al, 2008). Research has identified that recipients who are willing to consider living donation as an option perceive a lower risk of complications to the donor, believe that they would live longer following living transplantation, and believe more so than others that it is more appropriate to ask a family member to donate a kidney (Zimmerman, Albert, Llewellyn-Thomas, & Hawker, 2006).…”
Section: Communication Between Donors and Recipientsmentioning
confidence: 99%
“…Social support was measured using The Multidimensional Scale of Perceived Social Support (20) and augmented by asking participants if they usually attended doctors' appointments alone or with someone else. Familiarity with organ donation was determined by asking participants if they were registered as an organ donor, knew someone who had donated an organ, knew anyone who could potentially donate a kidney to them (7), and/or had been offered a kidney previously by a live donor (7). Ability to use technology to gain KT knowledge and to communicate with others regarding organ donation was determined by asking participants if they were comfortable using computers, email, and the internet.…”
Section: Participant Characteristics Ascertainmentmentioning
confidence: 99%